Frequencies of the Transferrin Alleles and Genotypes in Red Sokoto Goats of Nigeria (2014)
The aim of this study was to determine the frequencies of Transferrin alleles and genotypes in Red Sokoto goat. The present study was conducted on 96 adult Red Sokoto goat, maintained in the Northern parts of Nigeria and transported to Bodija market in Ibadan. The polymorphism of transferrin was determined using Cellulose Acetate electrophoresis technique. It was found that the transferrin was controlled by three codominant alleles (TfA, TfB, TfC) in Red Sokoto goats. These three alleles, because of the codominant nature of inheritance, control the occurrence of four transferrin genotypes in the analyzed flock. Two (TfAA and TfBB) of these were homozygous while the other two (TfAB and TfAC) were heterozygous. It was found that the TfAB genotype (0.562) was predominant while Tf AC genotype (0.021) was least common in the analyzed flock. Frequencies of other genotypes were as: TfAA (0.292) and TfBB (0.125) for each genotype in the population. The heterozygote genotype frequency (0.583) was more than that of homozygote genotype (0.417). Considerable variations were observed in the frequencies of transferrin alleles. The frequencies of transferrin alleles were found to be TfA = 0.583, TfB = 0.406 and TfC = 0.010. Transferrin system has showed genetic equilibrium in the analyzed population (x2 value = 4.414). The value of observed heterozygosity was 0.583 with average Fis value of - 0.1795